PENINGKATAN LITERASI SAINS MELALUI PROJEK BASED LEARNING PADA SISWA KELAS V MI NURUL ITTIHAD KOTA JAMBI - Ulkarmila, Safa; Saputra, Donal; Idris, Ilyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Scientific literacy is one of the essential competencies that needs to be developed in elementary school students to support critical thinking skills, problem solving, and decision making based on scientific evidence. However, teacher-centered learning processes have caused students’ involvement in science learning to remain suboptimal, so their scientific literacy still needs to be improved. This study aimed to improve the scientific literacy of fifth-grade students at MI Nurul Ittihad, Jambi City, through the implementation of the Project Based Learning (PjBL) model. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which consisted of planning, action, observation, and reflection stages. The research was conducted in two cycles with 19 fifth-grade students of MI Nurul Ittihad, Jambi City, as the subjects. Data were collected through observation, tests, and documentation, while the data were analyzed using quantitative descriptive and qualitative descriptive analysis. The results showed that the implementation of the Project Based Learning model was able to improve the quality of the learning process and students’ scientific literacy skills. Teacher activity increased from 69.12% in Cycle I to 96.32% in Cycle II. Students’ scientific literacy improved from 66.18% to 88.24%. The average learning outcome score also increased from 71.84 in the pre-cycle stage to 78.16 in Cycle I and 82.11 in Cycle II. The classical learning mastery percentage increased from 63.16% to 94.74%, indicating that the research success indicators had been achieved. Therefore, the implementation of the Project Based Learning (PjBL) model was proven effective in improving students’ scientific literacy in science learning in grade V of MI Nurul Ittihad, Jambi City.